PEMIKIRAN EKONOMI ABU ISHAQ AL-SYATIBI - Isma Tara; Puteri Lamsiah; Rezza Pramudipa; Dian Novita Dinata; Fitri Hayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the impact and relevance of Abu Ishaq Al-Syatibi's economic thinking in the context of modern economics. The method used is a qualitative approach with a literature study, identifying articles, books, and journals related to Al-Syatibi's main thoughts. The results of the study indicate that the concept of maqasid sharia put forward by Al-Syatibi contributed significantly to the development of Islamic economics, encouraging social welfare and justice. He divided human needs into three categories: dharuriyat, hajiyat, and tahsiniyat, which are the basis for resource management. This finding confirms that Al-Syatibi's thinking has influenced the development of a riba-free financial system, zakat management, and the principle of halal. In conclusion, Al-Syatibi's thinking remains relevant in facing the challenges of globalization, providing inspiration for more inclusive and sustainable economic policies, and emphasizing the importance of social justice and wealth redistribution.